Quantifying spatiotemporal patterns of urban expansion in three capital cities in Northeast China over the past three decades using satellite data sets - Sun, Yan; Zhao, Shuqing; Qu, Wenyuan (Environmental Earth Sciences, 2015)
Urban expansion is probably the most drastic form of land conversion and its impacts far transcend city's physical boundaries. Many studies have documented China's rapid urban expansion while the urban expansion in the traditional industrial base in Northeast China was understudied. Based on multi-temporal remote sensing images and landscape metrics, this study characterized the spatiotemporal patterns of urban land use changes in the metropolitan regions of three capital cities (i.e., Shenyang, Changchun and Harbin) in the Northeast China's traditional industrial base over the past three decades. The urban land in Shenyang, Changchun and Harbin expanded from 209.8, 202.0, and 239.6 km(2) in the late 1970s to 836.3, 682.4 and 567.9 km(2) in 2010, with an annual growth rate of 4.6, 4.0 and 2.6 %, respectively. The newly developed urban lands were largely distributed around the edge of urban districts. For all cities, the edge expansion was the dominant urban growth type (> 50 %), followed by infilling growth, and the proportion of outlying growth type was relatively low (< 20 %). City landscape became more complicated and fragmented, and landscape composition became evener. Despite these general similarities, there are differences in the magnitude and spatial patterns of urban expansion among three cities. Shenyang and Changchun generally had higher urban growth rates and expansion became compact earlier than Harbin. However, entering the twenty-first century, all cities went into a new era of urban expansion. Old industrial bases and newly established high-tech development districts have become urban expansion hotspots, and natural barriers to urban expansion weakened, stimulated by the policy of "Revitalizing Old Industrial Base of Northeast China". Managing the tradeoffs between urban expansion and environmental protection would be a great challenge for the local governments. National Natural Science Foundation of China [41071050, 31321061]; Scientific Research Foundation for the Returned Overseas Chinese Scholars, State Education Ministry SCI(E) EI SSCI ARTICLE sqzhao@urban.pku.edu.cn 11 7221-7235 73